1987
DOI: 10.1161/01.str.18.1.177
|View full text |Cite
|
Sign up to set email alerts
|

Water extraction fraction and permeability-surface product after intravenous injection in rats.

Abstract: S INCE Bolwig and Lassen 1 reported a procedure by which the water extraction fraction (WEF) in rat brain could be measured, various methodological improvements have been made. In these methods, however, the carotid artery is cannulated to introduce the tracers.w Cerebral blood flow (CBF) may change during cannulation or injection of tracers, and hence, changes in WEF may occur. Even using relatively new methods with i.v. injection of pHlwater, 4 -* rats must be sacrificed to measure the brain concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Whether primates differ from mammals in general is not known, because we Values are obtained from the literature (L) and the present study (P). Mean of four studies (Bailey et al, 2004;Hasegawa et al, 2010;Karbowski, 2007;Tajima et al, 1993); 11 Mean of four studies (Nakao et al, 2001;Ohno et al, 1979;Sakurada et al, 1978;Takagi et al, 1987); 12 Sato et al, 1999; 13 Macgowan et al, 2015;14 Christopher Macgowan (personal communication); ICA lumen radius from three mice; Foramen radius calculated from ICA lumen radius×1.4 (see note 6). are unable to gauge brain perfusion in other groups with the technique of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether primates differ from mammals in general is not known, because we Values are obtained from the literature (L) and the present study (P). Mean of four studies (Bailey et al, 2004;Hasegawa et al, 2010;Karbowski, 2007;Tajima et al, 1993); 11 Mean of four studies (Nakao et al, 2001;Ohno et al, 1979;Sakurada et al, 1978;Takagi et al, 1987); 12 Sato et al, 1999; 13 Macgowan et al, 2015;14 Christopher Macgowan (personal communication); ICA lumen radius from three mice; Foramen radius calculated from ICA lumen radius×1.4 (see note 6). are unable to gauge brain perfusion in other groups with the technique of this study.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the scaling of shear stress for the internal carotid artery from measured data from 70 kg humans (this study) and 375 g rats (Cai et al, 2012) using the shear stress equation and literature values. Blood flow rate in one internal carotid artery is taken as 3.83 cm 3 s −1 in humans (Boysen et al, 1970) and 0.028 cm 3 s −1 in rats (mean of four studies: Nakao et al, 2001;Ohno et al, 1979;Sakurada et al, 1978;Takagi et al, 1987). ICA lumen radius is taken as 0.221 cm in humans (mean of three studies: Kane et al, 1996;Krejza et al, 2006;Porsche et al, 2002) and 0.0304 in rats (Cai et al, 2012).…”
Section: Shear Stress (τ)mentioning
confidence: 99%
“…This hypothesis led to the following simplified equation: CBF=λ·ΔM·exp|D·ATT2α·M0t[]|1eJtJ+A·|JC+C·eJtJ·eCtJ·C·|JC1for ATTtATT+τ CBF=λ·ΔM·exp|D·ATT2α·M0t[]||1J+AJ|CJ|eJτ1eJtA·eCtC|CJ|eCτ11 normalfnormalonormalr tATT+τ, where t ′ = t‐ATT and t = τ + ω. Because ATT was 233 ms for the cortex and 177 ms for the striatum, according to Thomas et al , we used Equation for the cortex and Equation for the striatum, where A = PS/v bw , C = 1/T 1e , D = 1/T 1b , and J = A + D, with PS as the water permeability surface area product [PS = 155 mL · 100 g −1 · min −1 , ], T 1e as the T 1 of extravascular water and may be approximated by T1t, and v bw as the blood water volume fraction in the voxel, which correspond to 70% of the total blood volume fraction . For the total blood vo...…”
Section: Methodsmentioning
confidence: 99%
“…Measurements with tritiated water have shown that 70–90% of the water molecules in the blood perfusing the brain cross the blood–brain barrier and enter the brain tissues in a single pass ([chapter 4 in 16], [36–42]). If cerebral blood flow is 800 ml min −1 [43] then brain blood water flow, the water flow along the capillaries, is perhaps 0.85 × 800 ml min −1  = 680 ml min −1 (the rest is made up of solutes such as haemoglobin).…”
Section: Transfers Of Water O2 Co2 and Major Nutrients Between Bloomentioning
confidence: 99%